Antifungal and antibiofilm effect of duloxetine hydrochloride against Cryptococcus neoformans and Cryptococcus gattii - Rehem, Amanda Rodrigues [UNESP]; da Gama Viveiro, Letícia Rampazzo [UNESP]; De Souza Santos, Evelyn Luzia [UNESP]; do Carmo, Paulo Henrique Fonseca [UNESP]; da Silva, Newton Soares [UNESP]; Junqueira, Juliana Campos [UNESP]; Scorzoni, Liliana [UNESP] (Springer Nature, 2024)
Cryptococcosis is an invasive mycosis caused mainly by Cryptococcus gattii and C. neoformans and is treated with amphotericin B (AMB), fluconazole and 5-fluorocytosine. However, antifungal resistance, limited and toxic antifungal arsenal stimulate the search for therapeutic strategies such as drug repurposing. Among the repurposed drugs studied, the selective serotonin reuptake inhibitors (SSRIs) have shown activity against Cryptococcus spp. However, little is known about the antifungal effect of duloxetine hydrochloride (DH), a selective serotonin and norepinephrine reuptake inhibitor (SSNRI), against C. neoformans and C. gattii. In this study, DH inhibited the growth of several C. neoformans and C. gattii strains at concentrations ranging from 15.62 to 62.50 µg/mL. In addition, DH exhibited fungicidal activity ranging from 15.62 to 250 µg/mL. In biofilm, DH treatment reduced Cryptococcus spp. biomass at a level comparable to AMB, with a significant reduction (85%) for C. neoformans biofilms. The metabolic activity of C. neoformans and C. gattii biofilms decreased significantly (99%) after treatment with DH. Scanning electron micrographs confirmed the anti-biofilm activity of DH, as isolated cells could be observed after treatment. In conclusion, DH showed promising antifungal activity against planktonic cells and biofilms of C. neoformans and C. gattii, opening perspectives for further studies with DH in vivo.
Keywords: Biofilm; Cryptococcus spp; Drug repurposing; Duloxetine hydrochloride